Variability of perfluoroalkyl substance concentrations in pregnant women by socio-demographic and dietary factors in a Spanish birth cohort. (July 2016) - Manzano-Salgado, Cyntia B.; Casas, Maribel; Lopez-Espinosa, Maria-Jose; Ballester, Ferran; Martinez, David; Ibarluzea, Jesus; Santa-Marina, Loreto; Schettgen, Thomas; Vioque, Jesus; Sunyer, Jordi; Vrijheid, Martine
Abstract: Background: Prenatal exposure to perfluoroalkyl substances (PFAS) might affect child health; but maternal determinants of PFAS exposure are unclear. We evaluated the socio-demographic and dietary factors of prenatal PFAS concentrations in a Spanish birth cohort. Methods: We analyzed perfluorohexanesulfonic acid (PFHxS), perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA) in 1216 plasma samples collected during the 1 ST trimester of pregnancy (2003–2008). We used multivariable linear regressions to assess the geometric mean (GM) ratios of PFAS concentrations by socio-demographic and dietary factors. We used analysis of variance (ANOVA) to assess the variability of PFAS concentrations by maternal factors. Results: GM PFAS concentrations ranged from 0.55 ng/mL for PFHxS to 5.77 ng/mL for PFOS. Women born outside of Spain had lower PFAS concentrations (e.g. GM ratio for PFHxS 0.53[95%CI: 0.46, 0.60] than Spanish women. PFHxS and PFOA concentrations were higher in mothers from the regions of Sabadell (2.13[1.93, 2.35] and 1.73[1.60, 1.88], respectively) and Valencia (1.40[1.28, 1.54] and 1.42[1.31, 1.53], respectively) than Gipuzkoa. PFOA and PFNA concentrations decreased with parity (≥ 2 children: 0.79[0.67, 0.94] and 0.82[0.68, 0.99], respectively). Younger women (i.e. < 25 years) had lower PFHxS (0.73[0.62, 0.86]) and PFOS (0.85[0.75, 0.96]) concentrations than older women. PFHxS and PFOA concentrations were lower in women who previously breastfed for > 6 months compared to those who never breastfed (0.79[0.67, 0.94] and 0.82[0.71, 0.95], respectively). High intake of fish and shellfish during pregnancy (i.e. ≥ 5.6 servings/week) was associated with 11% (1.11[1.04, 1.18]) higher PFOS concentrations than the lowest intake group. Our ANOVA models explained 26% to 40% of PFAS concentrations variability. Conclusions: Prenatal PFAS concentrations were mainly determined by maternal country of birth, region of residence, previous breastfeeding and age. Fish and shellfish intake also contributed to PFOS and PFOA concentrations. Highlights: Pregnant women in Spain were ubiquitously exposed to PFAS during 2003–2008. Mean PFAS concentrations ranged from 0.55 ng/mL for PFHxS to 5.77 ng/mL for PFOS. Main PFAS predictors were maternal country of birth, region, breastfeeding and age. Fish and shellfish intake was the main dietary predictor of PFOS and PFOA.